Financial feasibility of biodiverse agroforestry arrangements: case study in Mato Grosso do Sul, Brazil (Research, Society and Development, 2021)
Aiming to provide aid for planning biodiverse Agroforestry Systems (AF), this paper presents an analysis of the financial viability of four different agroforestry models, in the experimental field of Escola Municipal Rural Benedita Figueiró, Ivinhema – MS county. The analyzed AF arrangements are composed of 45 forest species and 9 species for commercial purposes: Coffee + Banana System, Coffee with Forest System, Pineapple System and Cumari System. After surveying the costs of implementation, maintenance and expected revenues, a financial analysis was made for the period of 20 years, using AmazonSAF spreadsheet. Three models presented final positive net balance, but underperforming in the stability phase. The consortium of Forest Species with Coffee and Banana proved to be viable for recovery with financial return. Coffee favors the peoject´s long-term cash flow. The shortest time to return on investment was obtained in the Pineapple System, as it represents a short cycle culture. The adopted spacing generated an shading excess, indicating the need of selective trimming, int the 6th year, of arboreal individuals who are removing the solar incidence on the cultivable lines. In the system planning phase, it is suggested to insert annual crops between the lines of AF Coffee + Banana, to reduce the period of return on investment. Research should be explored in order to establish guidelines for the composition of biodiverse agroforestry models, which can serve as a reference for farmers to find security in this type of production.